The Clinical Outcomes of New Hyaluronan Nasal Dressing: A Prospective, Randomized, Controlled Study. Issue 1 (January 2013) - Shi, Runjie; Zhou, Jiaqing; Wang, Bingshun; Wu, Qingwei; Shen, Yuling; Wang, Peihua; Wang, Jiadong; Wang, Yunyun; Chen, Ying; Shu, Xiao Zheng
Background: Poor postoperative wound healing after endoscopic sinus surgery (ESS) remains a significant problem. This study evaluates the efficacy and safety of a new absorbable hyaluronan hydrogel. Methods: A prospective, randomized, controlled trial was conducted. Fifty-five patients with bilateral ESS were recruited and randomized to receive absorbable hyaluronan hydrogel in one side as treated and the opposite side without absorbable hyaluronan hydrogel as control. Clinical outcome measures were assessed at postoperative 1, 2, 4, 8, and 12 weeks. Results: Fifty-four patients completed the study. Overall, absorbable hyaluronan hydrogel significantly promotes the reepithelization process and reduces the presence of obstructing synechia, nonobstructing synechia, edema, crust, and mild mucopurulent drainage (all p ≤ 0.0002). At all postoperative follow-up visits, the promotion in reepithelization is statistically significant at 2, 4, and 8 weeks, and the reductions in the presence of nonobstructing synechia, edema, crust, and mild mucopurulent drainage are all statistically significant except for the presence of crust at 12 weeks and mild mucopurulent drainage at 1 and 12 weeks. Although the presence of obstructing synechia at each follow-up visit between groups does not reach statistical significance, the incidence ranges from 5.56 to 12.96% in the control group and from 0 to 3.70% in the treated group. No adverse event related to treatment was observed. Conclusion: In this clinical study, data analyses suggest that this new absorbable hyaluronan hydrogel, as nasal dressing/packing after ESS is safe and promotes the postoperative reepithelization process and reduces the presence of synechia, edema, crust, and mild mucopurulent drainage.